2020
DOI: 10.3390/jmse8040261
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Coelomic Fluid Extracts of the Sea Urchin Arbacia lixula Impair Mitochondrial Potential and Cell Cycle Distribution and Stimulate Reactive Oxygen Species Production and Autophagic Activity in Triple-Negative MDA-MB231 Breast Cancer Cells

Abstract: Triple-negative breast cancer (TNBC) is a highly malignant tumor histotype which lacks effective targeted therapies, thereby being considered as the most aggressive form of breast carcinoma. To identify novel compounds which could counteract TNBC cell growth, we explored the in vitro effects of crude extracts and <10 kDa-filtered fractions of the coelomic fluid obtained from the sea urchin Arbacia lixula on TNBC MDA-MB231 cells. We examined cell viability, cycle distribution, apoptotic/autophagic activity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…A specimen of the A. lixula sea urchin. Taken from [75].…”
Section: Autophagy Modulators From Echinodermatamentioning
confidence: 99%
See 2 more Smart Citations
“…A specimen of the A. lixula sea urchin. Taken from [75].…”
Section: Autophagy Modulators From Echinodermatamentioning
confidence: 99%
“…Both organisms have been widely used as models to examine the effects of anthropogenic chemical and noise pollution [78][79][80]. On the basis of the acknowledged diverse biological and pharmacological properties shown by the compounds and extracts from sea urchins and holothurians [82][83][84][85], in search of novel potential anti-breast cancer preparations, crude and <10 kDa-filtered fractions of cell-free aqueous extracts of the coelomic fluids from A. lixula and H. tubulosa were administered to MDA-MB231 TNBC cells, and the biological aspects of the observed cytotoxic effects were investigated [75,81].…”
Section: Autophagy Modulators From Echinodermatamentioning
confidence: 99%
See 1 more Smart Citation
“…The phylum Echinodermata, gathering invertebrates that display a radial symmetry, incorporates about 6000 living marine species around the globe. In recent years, echinoderms have attracted much attention as producers of biomolecules with promising anti-microbial, anti-protozoal, anti-fungal, and anticancer properties, making them potential candidates for drug development and future therapeutic applications [165][166][167][168]. Astropecten indicus (Döderlein, 1888; Asteroidea, Paxillosida: Astropectinidae; Figure 23), also called comb star or sand star, is a starfish that is distributed in the tropical environments of the Indo-Pacific area, and in particular of the United Arab Emirates, Qatar, Thailand, Gulf of Mannar, and Palk Bay region.…”
Section: Echinodermatamentioning
confidence: 99%
“…These products contribute to the adaptation mechanisms to the specific life conditions in the greatly different marine ecosystems [26]. A large proportion of invertebrate-derived extracts and isolated compounds has shown active pharmacological properties, such as anticancer, antimicrobial, and anti-inflammatory, among others, with an extensive spectrum of biomedical applications that makes them already approved or prospective drugs of marine origin with promising results for different therapeutic purposes [27][28][29][30][31][32]. Within this scenario, the aim of this review is to gather selected studies that reported the extraction and identification of marine invertebrate-derived chemicals that possess HDACi properties and recapitulate the molecular, biochemical, and/or physiological aspects, where available, which are associated with the examined molecules.…”
Section: A Brief Insight Into Histone Deacetylases and Histone Deacetylase Inhibitorsmentioning
confidence: 99%